Three-Dimensional Simulations of Optical Multimode Waveguides - Backhaus, Carsten; Loosen, Florian; Lindlein, Norbert (Springer International Publishing, 2022)
The waveguides fabricated in the project OPTAVER have a special shape with a circle segment cross section and are highly multimode due to the large extension of about 300 µm in diameter and about 40 µm in height. Therefore, specially adapted simulation methods have been developed. On the one side, due to the highly multimode nature, ray tracing can be used. Here, a quite efficient bisection algorithm has been investigated for the calculation of the intersection points with an arbitrarily curved waveguide during the propagation of light along its axis. On the other side, interference and diffraction effects can only be modeled by a wave-optical simulation. Here, the wave propagation method (WPM) is used which is also quite efficient compared to beam propagation methods. Especially, for a waveguide coupler (see chap. 6), this method gives more accurate results as a ray tracing simulation.
CRIS-Team Scopus Importer:2024-12-16